Comparison of the cellular transport mechanism of cationic, star-shaped polymers and liposomes in HaCat cells - Luo H (Dove Medical Press, 2017)
Heng-Cong Luo,1,2,* Na Li,1,* Li Yan,1 Kai-jin Mai,3 Kan Sun,1 Wei Wang,1 Guo-Juan Lao,1 Chuan Yang,1 Li-Ming Zhang,3 Meng Ren1 1Department of Endocrinology, Sun Yat-Sen Memorial Hospital, Guangdong Provincial Key Laboratory of Malignant Tumor Epigenetics and Gene Regulation Medical Research Center, Sun Yat-Sen University, Guangzhou, People’s Republic of China; 2Department of Endocrinology, The Third Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China; 3School of Materials Science and Engineering, School of Chemistry, Sun Yat-Sen University, Guangzhou, People’s Republic of China *These authors contributed equally to this work Abstract: Several biological barriers must be overcome to achieve efficient nonviral gene delivery. These barriers include target cell uptake, lysosomal degradation, and dissociation from the carrier. In this study, we compared the differences in the uptake mechanism of cationic, star-shaped polymer/MMP-9siRNA complexes (β-CD-(D3)7/MMP-9siRNA complexes: polyplexes) and commercial liposome/MMP-9siRNA complexes (Lipofectamine® 2000/MMP-9siRNA complexes: liposomes). The uptake pathway and transfection efficiency of the polyplexes and liposomes were determined by fluorescence microscopy, flow cytometry, and reverse transcriptase-polymerase chain reaction. The occurrence of intracellular processing was assessed by confocal laser scanning microscopy. Endosomal acidification inhibitors were used to explore the endosomal escape mechanisms of the polyplexes and lysosomes. We concluded that the polyplexes were internalized by non-caveolae- and non-clathrin-mediated pathways, with no lysosomal trafficking, thereby inducing successful transfection, while the majority of liposomes were internalized by clathrin-dependent endocytosis (CDE), caveolae-mediated endocytosis, and macropinocytosis, and only CDE induced successful transfection. Liposomes might escape more quickly than polyplexes, and the digestion effect of acidic organelles on liposomes was faint compared to the polyplexes, although both complexes escaped from endolysosomes via the proton sponge mechanism. This may be the key aspect that leads to the lower transfection efficiency of the β-CD-(D3)7/MMP-9siRNA complexes. The present study may offer some insights for the rational design of novel delivery systems with increased transfection efficiency but decreased toxicity. Keywords: β-CD-(D3)7, liposome, endocytosis, endolysosomal escape, intracellular trafficking